To increase learning for the understanding ones : reading and reconstructing the fragmentary early Jewish sapiential text 4QInstruction - Tigchelaar, Eibert J. C. (Studies on the Texts of the Desert of Judah, 2001)
This study aims at furthering our understanding of the early Jewish sapiential composition 4QInstruction which was found in fragmentary manuscripts at Qumran. The first part focuses on the reading and joining of the fragments, and gives an approximate reconstruction of the manuscripts and the composition. The second part discusses some disputed sections and themes in more detail, especially the beginning of the composition (4Q416 1), its relation to the Community Rule and the Hodayot, alleged sacerdotal fragments (4Q415 1 ii-2 I and 4Q418 81), as well as fragments describing fate after death (4Q418 55 and 69 ii). The first part is intended as a supplement to the official DJD edition, whereas the second part is of a more general interest.